2016
DOI: 10.6004/jnccn.2016.0163
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delays in Chemotherapy Initiation Among Patients With Breast Cancer at a Comprehensive Cancer Center

Abstract: This study provides insight into subpopulations that may be at risk to experience delays in chemotherapy initiation, directing interventions to improve the timeliness of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Wait times in the treatment of breast cancer have increased over the past 20 years, [1][2][3][4] in part as a result of the growing complexity of breast cancer management, including additional testing conducted to help guide treatment decisions. 3,5 Among patients with early-stage estrogen receptor (ER)positive and human epidermal growth factor receptor 2 (HER2)-negative breast cancer, the Oncotype DX Recurrence Score (RS; Genomic Health, Redwood City, CA), a multigene diagnostic test that provides 10-year estimates for risk of breast cancer recurrence and the potential benefit of chemotherapy, is used by oncologists to assist in adjuvant treatment decisions and is included in all major breast cancer clinical guidelines. [6][7][8] Incorporating Oncotype DX testing into clinical practice has been shown to limit unwarranted chemotherapy use, leading to decreased patient morbidity and reduced health care costs, [9][10][11][12] yet frequently introduces delays to treatment decision making and chemotherapy initiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wait times in the treatment of breast cancer have increased over the past 20 years, [1][2][3][4] in part as a result of the growing complexity of breast cancer management, including additional testing conducted to help guide treatment decisions. 3,5 Among patients with early-stage estrogen receptor (ER)positive and human epidermal growth factor receptor 2 (HER2)-negative breast cancer, the Oncotype DX Recurrence Score (RS; Genomic Health, Redwood City, CA), a multigene diagnostic test that provides 10-year estimates for risk of breast cancer recurrence and the potential benefit of chemotherapy, is used by oncologists to assist in adjuvant treatment decisions and is included in all major breast cancer clinical guidelines. [6][7][8] Incorporating Oncotype DX testing into clinical practice has been shown to limit unwarranted chemotherapy use, leading to decreased patient morbidity and reduced health care costs, [9][10][11][12] yet frequently introduces delays to treatment decision making and chemotherapy initiation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Incorporating Oncotype DX testing into clinical practice has been shown to limit unwarranted chemotherapy use, leading to decreased patient morbidity and reduced health care costs, [9][10][11][12] yet frequently introduces delays to treatment decision making and chemotherapy initiation. 3,5 Vandergrift et al 3 reported that Oncotype DX testing was associated with a 2.2-week increase in time to chemotherapy initiation. Similarly, we previously reported that patients undergoing RS testing were seven times more likely to wait longer than 6 weeks from last definitive breast surgery (LDS) to begin chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the impact of IBR on time to adjuvant chemotherapy reported a large variation in time to adjuvant chemotherapy, ranging from 21 to 80 days for those who had mastectomy alone and from 31 to 97 days for patients who received IBR, with reported differences between these cohorts of 14–27 days. However, this large variation may have been the result of the small single‐centre studies, weak methodology and biases, such as the lack of adjusting for treatment by indication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating Oncotype DX testing into clinical practice has been shown to limit unnecessary chemotherapy use, leading to decreased patient morbidity and reduced health care costs [7][8][9]. However, additional testing frequently introduces delays into treatment decision-making and chemotherapy initiation [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%